Secretory leucocyte protease inhibitor regulates bone metabolism and inflammation in experimental mouse periodontitis - Karin Sasagawa; Hisanori Domon; Satoru Hirayama; Tomoki Maekawa; Toshihito Isono; Koichi Tabeta; Yutaka Terao (Communications Biology)
Abstract Periodontitis is characterized by the activity of neutrophil elastase, a host defense factor that leads to the destruction of the epithelial barrier and bacterial invasion of the periodontal tissue. Secretory leukocyte protease inhibitors (SLPI), predominantly secreted by epithelial cells, diffuse into the mucosal surface and inhibit excessive tissue loss caused by elastase during inflammation. The SLPI level is high in healthy gingiva and low in severe periodontitis. In this study, we hypothesized that intragingival administration of SLPI inhibits periodontal tissue destruction caused by periodontitis. Administration of SLPI significantly reduced neutrophil elastase activity in periodontal tissue and alleviated alveolar bone loss in mice. Real-time PCR analysis revealed that SLPI administration downregulated the transcription of pro-inflammatory cytokines and osteoclast-related factors in the gingival tissue. Furthermore, in vitro treatment of bone marrow macrophages with SLPI resulted in the downregulation of osteoclast differentiation. SLPI treatment of MC3T3-E1 cells promoted osteoblast differentiation and bone formation. These findings suggest that SLPI protects against periodontal tissue damage by suppressing inflammation and bone resorption and promoting bone regeneration.